The role of time in the development of society in Islam - Turgunbayev Anvarjon Adhamjon ugli (Periodica Journal, 2023)
This article examines the importance of time in the context of social development within Islam. It explores the historical, cultural, and philosophical dimensions of time in Islamic civilization, highlighting how the concept of time influenced the growth and evolution of Muslim societies over the centuries.
Keywords: Islam; development; society; time